Perlindungan Konsumen Terhadap Penggunaan Bahan Pengawet Makanan Menurut Undang-Undang Nomor 8 Tahun 1999 Tentang Perlindungan Konsumen - Roida Nababan; Jinner Sidauruk; Besty Habeahan; Lesson Sihotang; Dakka Hutagaol (Jurnal Visi Pengabdian Kepada Masyarakat, 2021)
The use of hazardous materials used as food additives that are prohibited by the government is the main problem in the development of the goods and services industry, business actors will seek the highest profit without providing guarantees for the quality of goods and / or services produced and / or traded based on the provisions of goods quality standards and / or applicable services. The compensation in question can be in the form of health care and the provision of compensation to consumers who have been injured or their heirs or an agreement from the parties themselves. In carrying out every activity, the business actor is responsible for what it produces. Every violation of norms and several actions that are contrary to the aim of creating a healthy business climate can be categorized as illegal actions. Therefore, business actors will be subject to legal sanctions in the form of administrative, civil and criminal sanctions. This is regulated in Article 19 of Law of the Republic of Indonesia Number 8 of 1999 concerning Consumer Protection. Legal sanctions against food business actors who are proven to have committed an offense by using hazardous substances in the production process are carried out in the form of withdrawing food products, temporarily stopping production until the related problem is resolved and withdrawing food numbers from the household industry, destroying the food or drink if it is proven to endanger health. and human souls, and revocation of production permits or business permits.